Osmotic adjustment and yield of two varieties of avocado (Persea americana), Hass and Fuerte, with drip irrigation system, in Andean area of Peru - Quispe-Rodriguez, Juan (2024)
The cultivation of avocado (Persea Americana) is not only essential from an economic point of view, but also plays a crucial role in the nutrition, health and well-being of populations around the world. The study was carried out in Ayacucho -Peru (latitude: 12° 53' 57'' S, longitude: 74° 16' 55'' W and altitude: 2596 masl), with the objective of evaluating the effect of the use of the technical drip irrigation system on the production and yield of two varieties of avocado, Hass and Fuerte. The study was based on the use of an irrigation system with programming by treatment with avocado plants installed in plots of 500 m² in 6 sectors, with a density of 5 x 5 m, whose age was between 5 to 16 years, of the which were considered 12 plants (6 plants with drip irrigation and 6 plants as a control with gravity irrigation). Irrigation was carried out right at the flowering and production stage, guaranteeing adequate water supply in periods of water deficit, between February and June 2022. The experimental design was a complete randomized block, with six blocks of 20 plants each. The harvest carried out reported yields of 67.96 ± 8.8 t/ha under technical irrigation and 26.42 ± 4.93 t/ha under gravity irrigation, an increase of 157% with respect to the latter. As for the varieties, the Fuerte avocado had the highest yield 49.38 ± 23.06 t/ha compared to the Hass variety (45.0 ± 21.14 t/ha), the maximum yield occurred with drip irrigation for the Fuerte variety (71.09 ± 8.38 t/ha), this is explained by the energy expenditure in the osmotic adjustment potential which drastically decreases the yield potential with traditional gravity irrigation, obtaining a minimum yield in Hass of 25.18 ± 4.44 t/ha.